Engaged Anthropology and Scholar Activism: Double Contentions. Issue 1 (1st June 2022) - Rasch, Elisabet Dueholm; van der Hout, Floor; Köhne, Michiel
Abstract : This special issue explores theoretical and methodological issues related to activist and engaged scholarship. Combining scholarship and activism involves the (collaborative) production of knowledge that contributes not only to understanding the issues research participants face, but also to the social change they envision (Kirsch 2018; Hale 2006; Rasch and Van Drunen 2017; Rasch and Köhne 2016). Often, this entails a process of double contention. Activist scholars might be involved in social struggles against inequality and exclusion beyond the production of knowledge, engaging in solidarity work, supporting court cases, and co-strategizing for actions (see for example Bringa 2016; Grasseni 2014; Hale 2006). At the same time, they are often involved in processes of contention related to the metrics-oriented neoliberal university, as well as to its underlying positivist, eurocentrist, and colonialist structures (see for example Datta 2018; Mountz et al 2015).